The Influence of Perceived Food Risk and Source Trust on Media System Dependency - Sherrie R. Whaley; Mark Tucker (Journal of Applied Communications, 2004)
Consumers regularly identify food safety as an issue of great concern. They also consistently rank mass media as a primary source of food safety information. The purpose of this study was to investigate Ohioans’ levels of media system dependency and to assess the role of source trust and perceived food risk factors in influencing this dependency. Mail survey techniques were used to collect data from a sample of 7,976 Ohio residents. Data are reported for 4,014 respondents, for a 56 percent response rate. Traditional media, such as newspapers and television news, were perceived by respondents to be the most helpful among the media formats assessed. Moderate levels of perceived risk were found for the food safety items assessed. Pesticide residues in food and contamination of drinking water generated the highest levels of perceived risk. Relative to perceived source trust, physicians and scientists were evaluated most favorably, ahead of farmers and growers, the U.S. Department of Agriculture, and Extension. Regression findings indicate that perceived trust in government and expert sources were the two best predictors of media dependency, followed by perceived food safety risk. Findings have implications for food safety communicators and journalists communicating with at-risk audiences about the safety of their food supply.